Globalization: A Conceptual Debate - Hoshiar Marouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Since the beginning of the 1960s the international studies have begun to give a special interest to globalization. However, the differences that have arisen about the interpretation of this phenomenon, led to many complexities and situations of confusion. This fact is further exacerbated, because globalization appears for a long period of time and then disappears or diminishes according to the prevailing international conditions and the response of different economies to the most powerful centres in the world. The views of those concerned differed as to the extent to which certain definitions of globalization could be generalized to cover all their situations in terms of space and time or to address each situation differently, since what applied to a given situation differed in its characteristics from other situations. After introducing several definitions suggested by those interested in this concept, the author tried here to present a definition that may be more comprehensive than previous. And because the characteristics of this phenomenon are of great importance in defining the concept of globalization, these characteristics, were presented in order to prepare the reader to compare different ideas to identify this phenomenon, which requires more debate.